Do Rio Amazonas à Península Ibérica: viajando com o Barão de Marajó - SARGES, Maria de Nazaré dos Santos (Universidade Federal do Pará, 2019)
The article discusses about the trips from Amazon River to the Iberian Peninsula realized by Jose Coelho da Gama e Abreu, Barão de Marajó, a political and intellectual, and described in his book From the Amazon to the Seine, Nile, Danube and Bósphoro. Travel Notes published in 1874, seeking to reflect how the foreign relations were important during this period to set their own region, your country, yourself, increasing its "world-consciousness".